2017
DOI: 10.1371/journal.pone.0186352
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural characteristics of porcine hepatocytes donated after cardiac death and preserved with warm machine perfusion preservation

Abstract: The effects of warm machine perfusion preservation of liver grafts donated after cardiac death on the intracellular three-dimensional ultrastructure of the organelles in hepatocytes remain unclear. Here we analyzed comparatively the ultrastructure of the endomembrane systems in porcine hepatocytes under warm ischemia and successive hypothermic and midthermic machine perfusion preservation, a type of the warm machine perfusion. Porcine liver grafts which had a warm ischemia time of 60 minutes were perfused for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 83 publications
2
21
0
Order By: Relevance
“…The storage of energy in mitochondria during preservation is also important. Bochimoto et al [20] described the appearance of abnormal vacuoles and invagination of mitochondria in hepatocytes after 1 h warm ischemia by SEM. In the present study, the hepatocytes preserved by HMP showed extremely swollen mitochondria, while the SNMP+HbV groups had hepatocytes with healthy-looking mitochondria, abundant vacuoles, and membranous structures sequestrating cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage of energy in mitochondria during preservation is also important. Bochimoto et al [20] described the appearance of abnormal vacuoles and invagination of mitochondria in hepatocytes after 1 h warm ischemia by SEM. In the present study, the hepatocytes preserved by HMP showed extremely swollen mitochondria, while the SNMP+HbV groups had hepatocytes with healthy-looking mitochondria, abundant vacuoles, and membranous structures sequestrating cellular organelles.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of osmium macerated samples for observation by a scanning electron microscope was described previously [20]. In brief, a fixative mixture of 0.5% PFA and 0.5% glutaraldehyde in 0.1 MPB (pH 7.4) was macerated with liver samples for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Osmium maceration was applied as described (Bochimoto et al, ). Briefly, colon blocks were immersed in 1% OsO 4 for 6 hr followed by 25 and 50% dimethyl sulfoxide, frozen with a flat aluminum block precooled in liquid nitrogen, and broken into two pieces using a screwdriver and a hammer.…”
Section: Methodsmentioning
confidence: 99%
“…Osmium‐maceration scanning electron microscopy (SEM) allows visualization of three‐dimensional ultrastructural architectures after removing soluble protein (Bochimoto et al, ; Koga, Bochimoto, Kusumi, Ushiki, & Watanabe, ; Tanaka & Naguro, ). The present study compared colonic epithelial cells in rat models of IBD induced by TNBS and control rats using TEM and osmium‐maceration SEM to identified detailed ultrastructural changes.…”
Section: Introductionmentioning
confidence: 99%
“…The three‐dimensional (3D) ultrastructure of intracellular organelles has been investigated by scanning electron microscopy with osmium‐maceration (OM‐SEM) (Bochimoto et al, 2017; Koga, Bochimoto, Kusumi, Ushiki, & Watanabe, 2017). The 3D architecture of membranous organelles such as mitochondria, rough endoplasmic reticulum (rER), and Golgi apparatus can be assessed at high magnification after soluble protein is removed using a dilute solution of osmium.…”
Section: Introductionmentioning
confidence: 99%